Folk Romance in Pakistani Culture - Isar Kamran (بازیافت, 2022)
In Pakistani folk culture, romance appears as a symbol to unfold the deep insight and metaphysical expression regarding Heer Ranja, Soni Mahiwal, Mirza Sabhian and Sussi Punu. The important point regarding these folklore romance,, the divinity of love appears as the gift of Allah, create an unseen spirit to reach to its destiny. While observing every case,, the annihilated phenomenon unfold the metaphysical trait in the form of fana- which is an Arabic word means-passing away.Pakistani folklore is comprised of folk songs, folk tales, myth, legends, customs, proverbs and traditions of the four provinces and along with tribal areas forming the modern nation of Pakistan. Every village had hundreds of tales and traditions. The Pakistani folk lore is shaped by means of language and the traditions of various ethnic groups. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" Priority="50" Name=